L-carnitine alleviated acute lung injuries induced by potassium dichromate in rats: involvement of Nrf2/HO-1 signaling pathway. Issue 6 (June 2021) - Salama, Abeer; Fayed, Hany M.; Elgohary, Rania
Abstract: The activation of the Nrf2/HO-1 signaling pathway regulates cellular antioxidant stress and exerts anti-inflammatory and cytoprotective effects against acute lung injury (ALI). The present study aimed to evaluate the therapeutic role of L-carnitine (LC) against potassium dichromate (PD) - induced acute lung injury in adult male albino rats via modulation of Nrf2/HO-1 signaling pathway. For this purpose, forty rats were randomly allocated into 5 groups (8 rats each). The normal group received intranasal (i.n.) saline, while the ALI group received intranasal instillation of PD as a single dose of 2 mg/kg. The 3d – 5th groups received PD then after 24 h administered L-carnitine (25, 50 and 100 mg/kg; orally) for 3 consecutive days. The therapeutic effect of L-carnitine was evaluated by assessment of serum levels of glutathione (GSH) and malondialdehyde (MDA) along with measurement of lung contents of transforming growth factor β1 (TGFβ1), protein kinase B (AKT), Nuclear factor erythroid-2 related factor 2 (Nrf2), Kelch-like ECH-associated protein 1 (Keap1), heme oxygenase-1 (HO-1), NAD(P)H quinone oxidoreductase 1 enzyme (NQO1) and glutathione cysteine ligase modifier subunit (GCLM) expression. Post-treatment with L-carnitine effectively increased the levels of GSH and AKT, elevated Nrf2 and its target genes and decreased the levels of MDA and TGFβ1 in comparison with PD control rats. Additionally, L-carnitine effectively reduced the number of goblet cell, inhibited the mucus formation in bronchioles and interstitial inflammatory infiltrate as well as alleviated the destruction of alveolar walls, and the congestion of blood vessels in lung tissue induced by PD. Our findings showed that L-carnitine may be a promising therapeutic agent against PD-induced acute lung injury. Abstract : L-carnitine; Chromium; Acute lung injury; Nrf2; Keap1; HO-1; NQO1; GCLM.